Validation of the Aeolus L2B Rayleigh winds and ECMWF short‐range forecasts in the upper troposphere and lower stratosphere using Loon super pressure balloon observations. (8th November 2022) - Bley, Sebastian; Rennie, Michael; Žagar, Nedjeljka; Pinol Sole, Montserrat; Straume, Anne Grete; Antifaev, James; Candido, Salvatore; Carver, Robert; Fehr, Thorsten; von Bismarck, Jonas; Hünerbein, Anja; Deneke, Hartwig
Abstract: The novel Aeolus satellite, which carries the first Doppler wind lidar providing profiles of horizontal line‐of‐sight (HLOS) winds, addresses a significant gap in direct wind observations in the global observing system. The gap is particularly critical in the tropical upper troposphere and lower stratosphere (UTLS). This article validates the Aeolus Rayleigh–clear wind product and short‐range forecasts of the European Centre for Medium‐Range Weather Forecasts (ECMWF) with highly accurate winds from the Loon super pressure balloon network at altitudes between 16 and 20 km. Data from 229 individual balloon flights are analysed, applying a collocation criterion of 2 hr and 200 km. The comparison of Aeolus and Loon data shows systematic and random errors of − - 0.31 and 6.37 m · s − 1 ^-1 , respectively, for the Aeolus Rayleigh–clear winds. The horizontal representativeness error of Aeolus HLOS winds (nearly the zonal wind component) in the UTLS ranges from 0.6–1.1 m · s − 1 ^-1 depending on the altitude. The comparison of Aeolus and Loon datasets against ECMWF model forecasts suggests that the model systematically underestimates the HLOS winds in the tropical UTLS by about 1 m · s − 1 ^-1 . While Aeolus winds are currently considered as point winds by the ECMWF data assimilation system, the results of the present study demonstrate the need for a more realistic HLOS wind observation operator for assimilating Aeolus winds. Abstract : Rayleigh–clear winds from ESA's Doppler wind lidar mission Aeolus are validated against winds from the Loon super pressure balloon network and the ECMWF model forecast in the tropical upper troposphere and lower stratosphere (UTLS). The comparison of Aeolus and Loon datasets against ECMWF model forecasts suggests that the model systematically underestimates the HLOS winds in the tropical UTLS by about 1 m · s − 1 ^-1 . While Aeolus winds are currently considered as point winds by the ECMWF data assimilation system, the results of the present study demonstrate the need for a more realistic HLOS wind observation operator for assimilating Aeolus winds.